Pemanfaatan Ampas Kopi dan Arang Sekam Sebagai Media Tanam Dalam Pertumbuhan Tanaman Pakcoy (Brassica rapa L) - Indah, Nur; Jamaluddin; Lestari, Nunik (Agricultural Technology Education Study Program, 2023)
Discarded coffee grounds are unfortunate, considering they have potential as a planting medium because they contain compounds that can support plant growth. Likewise, husk charcoal provides benefits because it has a porosity which can bind water and has the nutrients needed by pakcoy plants. This study aims to analyze the utilization of coffee grounds and husk charcoal as a planting medium for the growth of pakcoy plants. This study used a Completely Randomized Design (RAL) with six treatments and three replications. The treatments applied are control (M0) 100% soil, (M1) 40% soil + 10% coffee grounds + 50% husk charcoal, (M2) 40% soil + 20% coffee grounds + 40% husk charcoal, (M3) 40% soil + 30% coffee grounds + 30% husk charcoal, (M4) 40% soil + 40% coffee grounds + 20% husk charcoal, (M5) 40% soil + 50% coffee grounds + 10% husk charcoal. The changes observed were plant growth (plant height, number of leaves, length of roots, total fresh weight of the plant, dry weight and chlorophyll levels. The best planting medium in the M1 treatment is a combination of 40% soil + 10% coffee grounds, and +50% husk charcoal. From the study results, it can be concluded that coffee grounds and husk charcoal can be used as a planting medium for the growth of pakcoy plants